Multiple HPV genotype infection impact on invasive cervical cancer presentation and survival - Nogueira Dias Genta, Maria Luiza (PLoS One, 2017)
BACKGROUND: Invasive cervical cancer (ICC) is the third most common malignant neoplasm affecting Brazilian women. Little is known about the impact of specific HPV genotypes in the prognosis of ICC. We hypothesized that HPV genotype would impact ICC clinical presentation and survival. METHODS: Women diagnosed with ICC at the Instituto do Câncer do Estado de São Paulo (ICESP) between May 2008 and June 2012 were included in the study and were followed until December 2015. HPV genotype was detected from formalin-fixed paraffin-embedded (FFPE) tumor tissue samples using Onclarity™ system (BD Viper™ LT automated system). RESULTS: 292 patients aged 50±14 years were analyzed. HPVDNA was detected in 84% of patients. The HPV genotypes studied were: HPV16 (64%), HPV18 (10%), HPV33-58 (7%), HPV45 (5%), HPV31 (4%) and other high-risk HPV genotypes (11%). HPV genotypes showed different distributions regarding histological type and clinical stage. Patients were followed for 35±21 months. The overall survival at 5 years after diagnosis of cervical cancer was 54%. Age, clinical staging, histological type and multiple HPV genotypes infection detected in the same tumor specimen were associated with poorer overall survival on multivariate Cox proportional hazard analysis (p<0.05). No specific HPV genotype affected survival. CONCLUSION: Multiple HPV genotype infection was associated with poorer ICC survival in our study, compared with single genotype infection. HPV genotyping from FFPE tumor tissue using an automated assay such as the Onclarity BD™ assay provides a simpler alternative for routine clinical use. IMPACT: This is the largest study employing an automated HPV genotyping assay using FFPE of ICC. Multiple HPV genotype infection adversely influenced survival.